Plant cell wall chemistry: implications for ruminant utilisation - X. Li (Journal of Applied Animal Nutrition, 2021)
Ruminants have adapted to cope with bulky, fibrous forage diets by accommodating a large, diverse microbial population in the reticulo-rumen. Ruminants are dependent on forages as their main sources of energy and other nutrients. Forages are comprised of a complex matrix of cellulose, hemicellulose, protein, minerals and phenolic compounds (including lignin and tannins) with various linkages; many of which are poorly defined. The composition and characteristics of polysaccharides vary greatly among forages and plant cell walls. Plant cell walls are linked and packed together in tight configurations to resist degradation, and hence their nutritional value to animals varies considerably, depending on composition, structure and degradability. An understanding of the inter-relationship between the chemical composition and the degradation of plant cell walls by rumen microorganisms is of major economic importance to ruminant production. Increasing the efficiency of fibre degradation in the rumen has been the subject of extensive research for many decades. This review summarises current knowledge of forage chemistry in order to develop strategies to increase efficiency of forage utilisation by ruminants.